Availability of phosphorus recovered from waste streams to plants cultivated in soilless growing media. Issue 6 (27th October 2021) - Hauck, Daniel; Lohr, Dieter; Meinken, Elke; Schmidhalter, Urs
Abstract: Background: Using secondary phosphorus (P) sources recovered from waste streams for base fertilization of soilless growing media may help conserve the global phosphate resources. However, little is known regarding the plant availability of P from secondary sources for soilless plant production. Aim: The objective of this study was to investigate the plant availability of P from secondary sources using a peat‐based growing medium and standard extraction methods. Methods: Seventeen secondary P sources differing in terms of feedstock and processing were tested, and their fertilization efficacy was compared with that of water‐soluble monocalcium phosphate (MCP‐P) in a pot experiment using marigolds. The correlation of plant P uptake with calcium chloride + diethylenetriaminepentaacetate (CAT) and/or calcium–acetate–lactate (CAL) extractable P amount in the growing medium ( P CAT and P CAL, respectively) was examined. Results: Only three of the 17 tested secondary P sources (all struvite forms) exhibited comparable fertilization efficacy to MCP‐P. The remaining sources showed P uptake varying between 4% and 91% of MCP‐P. For precipitates from liquid waste streams and untreated organic waste, except for sewage sludge and compost, the P uptake ranged from 71% to 100%. The highest variability (4%–86%) was observed for thermally and thermochemically treated secondary P sources. Plant P uptake was closely correlated with P CAT ( R 2 = 0.76) and P CAL ( R 2 = 0.78), and this correlation became even stronger when P CAT and P CAL were combined ( R 2 = 0.89). Conclusions: Most struvite forms meet the requirements of base P fertilization for soilless plant production and can substitute water‐soluble fertilizers obtained from primary P sources. The combination of P CAT and P CAL may be a promising approach to characterize the plant availability of P from secondary sources in soilless growing media and warrants further consideration.